2017
DOI: 10.1007/s11356-017-8803-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between level of urinary trace heavy metals and obesity among children aged 6–19 years: NHANES 1999–2011

Abstract: Global prevalence of obesity has been increasing dramatically in all ages. Although traditional causes for obesity development have been studied widely, it is unclear whether environmental exposure of substances such as trace heavy metals affects obesity development among children and adolescents so far. Data from the National Health and Nutrition Examination Survey (1999-2011) were retrieved, and 6602 US children were analyzed in this study. Urinary level of nine trace heavy metals, including barium, cadmium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 40 publications
8
40
2
1
Order By: Relevance
“…The body content of Cd assessed by urinary and/or blood Cd levels showed an inverse association with body mass index (BMI), central obesity, and risks of weight gain, and obesity in both children and adults. These have consistently been observed across populations, including the U.S., Belgium, Canada, Korea, and China [ 77 , 141 , 142 , 143 , 144 , 145 , 146 ]. In the U.S. NHANES 1999–2002 participants, an inverse association between body burden (urinary Cd levels) and central obesity was noted [ 141 ], while an inverse association between blood Cd and BMI was seen in the NHANES 2003–2010 participants [ 142 ].…”
Section: Measurement Of Effects Of Cadmium On Kidneysmentioning
confidence: 73%
“…The body content of Cd assessed by urinary and/or blood Cd levels showed an inverse association with body mass index (BMI), central obesity, and risks of weight gain, and obesity in both children and adults. These have consistently been observed across populations, including the U.S., Belgium, Canada, Korea, and China [ 77 , 141 , 142 , 143 , 144 , 145 , 146 ]. In the U.S. NHANES 1999–2002 participants, an inverse association between body burden (urinary Cd levels) and central obesity was noted [ 141 ], while an inverse association between blood Cd and BMI was seen in the NHANES 2003–2010 participants [ 142 ].…”
Section: Measurement Of Effects Of Cadmium On Kidneysmentioning
confidence: 73%
“…Recently, Ba exposure during pregnancy (assessed by measuring Ba concentrations in maternal hair and in fetal placenta) has been dose-dependently linked with the risk of congenital heart defects in offspring, underlying health hazards deriving from prenatal and transplacental exposure to this metal [93]. Furthermore, data from the National Health and Nutrition Examination Survey (NHANES 1999(NHANES -2011 found, in a large cohort of US children aged 6-19 years, a strong association between Ba exposure (urinary Ba concentration) and obesity [21].…”
Section: Discussionmentioning
confidence: 99%
“…Children are particularly vulnerable, in terms of biological effects, when exposed to metal pollution [13][14][15][16][17], mainly due to oxidative damage following chronic exposure [18,19]. In pediatric age, the body burden of metals has been linked with a number of pathologic conditions including nononcologic diseases (i.e., altered growth and development [20], obesity [21,22], and neurologic [23][24][25], cognitive [26], and respiratory [19,27] disorders) and cancer [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals that enter the human body through chronic exposure are very difficult to metabolize or decompose, so they accumulate in all tissues and organs over the years and exert chronic damage to the body when they reach a certain threshold (Raehsler et al, 2018). Epidemiological investigations have shown that heavy metals can be detected in the blood, urine, hair, and nails of healthy and diseased people and that the content is correlated with severity of respiration diseases (Wu et al, 2018), cardiovascular diseases (Lamas et al, 2016), neurodegeneration (Bjorklund et al, 2018a;Ghazala et al, 2018;Iqbal et al, 2018) diseases, autism spectrum disorder (Bjorklund et al, 2018b), and obesity (Park et al, 2017;Shao et al, 2017;Wang et al, 2018). Great efforts have been made to reduce heavy metal pollution, but these efforts often have very limited effects (Bisanz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%